Interaction design and physical computing in the era of miniature embedded computers - Arnan Sipitakiat (2018)
ACM 978-1-4503-1918-8/13/06. This paper describes a new paradigm as well as a new platform which have been developed to demonstrate new robotics and physical computing programming models that are now possible as a result of miniature single-board computers. Here we investigate new design opportunities that bring with them the ability to embed an entire computer, such as the Raspberry Pi, within an interactive project. We call our new platform the "embedded computer" model, and we utilize the proposed Pi-Topping framework to demonstrate several cases in which the platform has already been employed. The new platform consists of a hardware add-on for the Raspberry Pi and, to drive and program the platform, a modified version of the Scratch programming environment. Smartphones are used as a portable screen that offers a touch sensitive input capacity. Case studies that demonstrate the new design possibilities are then described.